Progress in Pluronic F127 Derivatives for Application in Wound Healing and Repair - Li S; Yang C; Li J; Zhang C; Zhu L; Song Y; Guo Y; Wang R; Gan D; Shi J; Ma P; Gao F; et al. (International Journal of Nanomedicine, 2023)
Shanshan Li,1,* Cheng Yang,1,* Junqiang Li,1,* Chao Zhang,1 Liaoliao Zhu,1 Yang Song,1 Yongdong Guo,1 Ronglin Wang,1 Dongxue Gan,1 Jingjie Shi,1 Peixiang Ma,1 Fei Gao,2 Haichuan Su1 1Department of Oncology, The Second Affiliated Hospital, Air Force Medical University, Xi’an City, People’s Republic of China; 2Center for Peptide Functional Materials and Innovative Drugs, Institute of Translational Medicine, Shanghai University, ShangHai City, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haichuan Su, Department of Oncology, The Second Affiliated Hospital, Air Force Medical University, No. 569 Xinsi Road, Baqiao District, Xi’an City, People’s Republic of China, Email suhc@fmmu.edu.cn Fei Gao, Center for Peptide Functional Materials and Innovative Drugs, Institute of Translational Medicine, Shanghai University, No. 99 ShangDa Road, BaoShan District, ShangHai City, People’s Republic of China, Email flyhightly@shu.edu.cnAbstract: Pluronic F127 hydrogel biomaterial has garnered considerable attention in wound healing and repair due to its remarkable properties including temperature sensitivity, injectability, biodegradability, and maintain a moist wound environment. This comprehensive review provides an in-depth exploration of the recent advancements in Pluronic F127-derived hydrogels, such as F127-CHO, F127-NH2, and F127-DA, focusing on their applications in the treatment of various types of wounds, ranging from burns and acute wounds to infected wounds, diabetic wounds, cutaneous tumor wounds, and uterine scars. Furthermore, the review meticulously examines the intricate interaction mechanisms employed by these hydrogels within the wound microenvironment. By elucidating the underlying mechanisms, discussing the strengths and weaknesses of Pluronic F127, analyzing the current state of wound healing development, and expanding on the trend of targeting mitochondria and cells with F127 as a nanomaterial. The review enhances our understanding of the therapeutic effects of these hydrogels aims to foster the development of effective and safe wound-healing modalities. The valuable insights provided this review have the potential to inspire novel ideas for clinical treatment and facilitate the advancement of innovative wound management approaches.Keywords: Pluronic F127, F127-CHO, F127-NH2, F127-DA, wound healing and repair